Ancient Lithuanian calendar festivals - Vaicekauskas, Arūnas (Vytautas Magnus University, 2014)
The book discusses traditional Lithuanian calendar festivals, their development, rituals, and customs. It also focuses on the ways rural communities celebrated Christmas, St John's Day, and St George's Day, paying special attention to ancient rituals that are still practiced today. The reader will also find answers to the following questions: What is the difference between Shrovetide and other calendar festivals? Why can Easter, which reached Lithuania with Christianity, reveal the customs of early Lithuanians no worse than other traditional rural festivals of pre-Christian origin? The book is dedicated to everyone interested in traditional Lithuanian culture and customs.